The Effect of Clinical Supervision Training on Increasing Compliance with the Five Moments of Hand Hygiene - Julianingsih, Sri Redjeki; Suartana, I wayan; Setiawan, Wawan; Kustiko, Wayan; Marni, Marni (Indonesian Journal of Global Health Research, 2024)
Hand hygiene aims to minimize and eliminate microorganisms from the palms of the hands and prevent the risk of infection due to health services so that patient safety can be guaranteed. Research purposes/ Objective: To determine the effect of clinical supervision training on compliance with the five moments of hand hygiene among health workers at Marzoeki Mahdi Hospital. Method: Design research with a quasi-experimental design, one group pretest – posttest design. Population: All Nurse at Marzoeki Mahdi Hospital . The samples in this study were executive nurses, room heads, nursing team leaders and Infection Prevention Control Link Nurse (IPCLN) at Marzoeki Mahdi Hospital Bogor. The sampling technique uses Stratified Random Sampling. Data collection techniques use research instruments consisting of observation sheets and questionnaires. A validity test with a value of 0.700 is said to be valid because it is > 0.297. Meanwhile, the reliability test analysis with a total Cornbach Alpha value of 0.736 is said to be reliable because it is reliable if the Cronbach Alpha value is >0.60. Data were analyzed using Univariate, Bivariate Analysis. With the Wilcoxon Non-Parametric Test. And Multivariate Analysis uses the Simultaneous F Test (Anova). Results: The significance value for pretest and posttest is 0.000 (<0.05). Conclusions : There is an Effect of Clinical Supervision Training on Increasing Five Moment Hand Hygiene Compliance